The effects of phonological skills and vocabulary on morphophonological processing. Issue 2 (April 2018) - Boersma, Tiffany; Baker, Anne; Rispens, Judith; Weerman, Fred
Morphophonological processing involves the phonological analysis of morphemes. Item-specific phonological characteristics have been shown to influence morphophonological skills in children. This study investigates the relative contributions of broad phonological skills and vocabulary to production and judgement accuracies of the Dutch past tense and diminutive, two morphophonological processes. Typically developing children (age 5;0–10;0, N = 114) were asked to produce and judge real and nonce diminutives and regular past tenses. Phonological processing skills were measured using a phonological awareness, digit span and nonword repetition task; vocabulary using the PPVT. Phonological skills and vocabulary contributed significantly to the production and judgement of the past tense and diminutive. The results underline the relation between phonological skills and the lexicon and the processing of morphophonology. These findings go further than showing the importance of the item-specific phonological context of the stem and suffix: they indicate that more general skills in the domain of phonology and vocabulary are involved.